Fatty Acid Composition of Cladosporium resinae Grown on Glucose and on Hydrocarbons - Cooney, J. J. (1971)
Cladosporium resinae was grown in submerged cultures on glucose; on Jet-A commercial aviation fuel; and on a series of n-alkanes, n-decane through n-tetradecane. Cell yield was greatest on glucose and least on Jet-A; n-alkanes were intermediate. Among n-alkanes cell yield decreased as chain length increased, except for n-dodecane, which supported less growth than n-tridecane or n-tetradecane. The total fatty acids of stationary-phase cells were analyzed by gas-liquid chromatography. In all cases the predominant fatty acids were 16:0, 18:1, and 18:2. The fatty acid composition of glucose-grown cells was similar to that of hydrocarbon-grown cells. Cells grown on n-tridecane or n-tetradecane yielded small amounts of acids homologous to the carbon source, but a similar correlation was not noted for n-decane, n-undecane, or n-dodecane. Cells grown on n-undecane or n-tridecane contained more odd-carbon fatty acids than cells grown on the other substrates, and the effect was more pronounced in n-tridecane-grown cells. Thus, the fatty acids of this organism are derived chiefly from de novo synthesis rather than from direct incorporation of oxidized hydrocarbons. The extent of direct incorporation increases as the chain length of the hydrocarbon growth substrate is increased.